(untitled) (Indian Journal of Animal Production and Management, 2015)
An investigation was carried out to study the managemental practices adopted by the rural dairy farmers of Kamrup, Nalbari, Barpeta and Goalpara district of Assam in rearing indigenous and crossbred cows. The majority of dairy farmers used thatch as roofing material in their cattle shed (56.84% and 81.48% in crossbred and indigenous cows Managemental practices adopted by dairy farmers respectively). Majority cattle sheds were observed with half wall (47.95%) for crossbred cows and full wall (62.96%) for indigenous cows. Concrete floor and earthen floor cattle shed were observed for crossbred cows as 67.81 per cent and 90.74 per cent for indigenous cows respectively. Proper drainage facilities in the sheds for crossbred cows (65.75%) and without proper drainage facilities for indigenous cows (88.89%) were also observed. Stall feeding was observed as 58.22 per cent in crossbred cows while grazing was observed as 92.59 per cent in indigenous cows. Most of the farmers fed their cows with naturally grown green fodder (94.52 and 96.30% in crossbred and indigenous cows respectively). The main source of dry fodder was paddy straw (Oryza sativa L.) and fed to the animals @ 2-5 kg per milch animal per day. Concentrate ration was provided @ 3-7 kg per crossbred cow per day; while for indigenous cows, 62.96 per cent of dairy farmers offered only rice polish @ 1-3 kg per cow per day and 37.04 per cent of dairy farmers did not provide concentrate ration to their cows at all.